พฤติกรรมด้านความเค้น - ความเครียดของยางธรรมชาติ - บุษยพรรณ อนุชน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purpose of this thesis is to study the relationship between stress and strain of natural rubber material. The behavior of the material was modeled using the Yeoh model. This study aims to determine the coefficients of the Yeoh model. The behavior of the material deformation was studied under three conditions, uniaxial tensile testing, planar shear testing and equi-biaxial tensile testing. For the biaxial tensile testing an apparatus was devised which can be used in conjunction with a universal testing machine (UTM). Five test specimens were prepared from natural rubber flat plate with a thickness of 2 mm. After testing under the three conditions, the relationship between stress and strain can be used to predict the behavior of the material by using the Yeoh model. This study found that the three coefficients of the Yeoh model can predict the deformation of natural rubber material from gain traction until almost torn. The data is within acceptable error (R2) limits. Natural rubber materials show anisotropic behavior. Therefore the coefficients obtained can only be used under the conditions they were obtained from. For example the uniaxial tensile testing coefficient can only be used under uniaxial tensile stress. The material tested isn’t the same in all directions. The material property depends on the molecular structure of the material. The hypothesis of this research has assumed that the material is isotropic so that the coefficients of each test are necessarily different. It can’t use the deformation effects of one test to predict the deformation behavior of a different testing condition.